2018
DOI: 10.1002/nau.23894
|View full text |Cite
|
Sign up to set email alerts
|

Injecting RNA interference lentiviruses targeting the muscarinic 3 receptor gene into the bladder wall inhibits neurogenic detrusor overactivity in rats with spinal cord injury

Abstract: Aims To investigate the effects of injecting RNA interference (RNAi) lentiviruses targeting the muscarinic 3 (M3) receptor gene into the bladder wall on bladder activity in rats with spinal cord injury (SCI). Methods Four M3 RNAi lentiviruses were constructed and used to infect primary cultured bladder smooth muscle cells (BSMCs). Western blotting and quantitative reverse transcription polymerase chain reaction (qRT‐PCR) were performed to determine the optimal RNAi lentivirus with the highest interference effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Previous studies have shown that SCI induces high bladder pressure voiding because of DO and urethral obstruction due to DSD, 10 which is associated with the overexpression of muscarinic receptors and the enhancement of acetylcholine release from parasympathetic nerve terminals. 22 Shang et al 23 revealed that the interference of muscarinic M3 receptors in SCI rats resulted in the improvement of DO. In this study, nintedanib reduced the expression of M2 and M3 receptors although these changes were prominent in the mucosa rather than the detrusor at 4 weeks after SCI in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SCI induces high bladder pressure voiding because of DO and urethral obstruction due to DSD, 10 which is associated with the overexpression of muscarinic receptors and the enhancement of acetylcholine release from parasympathetic nerve terminals. 22 Shang et al 23 revealed that the interference of muscarinic M3 receptors in SCI rats resulted in the improvement of DO. In this study, nintedanib reduced the expression of M2 and M3 receptors although these changes were prominent in the mucosa rather than the detrusor at 4 weeks after SCI in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of the analyzed reports, 74%, use spinal cord injury as an NDO model ( Figure 2 B). From these publications, 59% report complete transection of thoracic segments to induce SCI [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 38 , 39 , 43 , 44 , 46 , 48 , 49 , 50 , 55 , 57 , 62 , 63 ], followed by spinal contusion (13%). The use of spinal hemisections was less frequent (10%) [ 42 , 47 , 52 ], as were spinal compressions (8%) [ 32 , 36 , 54 , 56 ] and other SCI methods (10%) [ 41 , 51 , 53 , 58 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…All experimental procedures were implemented in compliance with the National Institute of Health Guidelines for the Care and Use of Laboratory Animals (2) and approved by the Institutional Animal Care and Use Committee of Xuanwu Hospital Capital Medical University (No. 20190128).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…It has been estimated that 250,000 to 500,000 people worldwide are suffering from spinal cord injury and approximately 81% of these patients experience different levels of neurogenic bladder (NB) which is one of the leading causes of their morbidity (1,2). Specifically, detrusor overactivity and detrusor-sphincter dyssynergia are typical NB urodynamic findings, and are diagnosed in 95% and 68% of spinal cord-injured (SCI) patients, respectively (3).…”
Section: Introductionmentioning
confidence: 99%